REVISITING THE SOCIOECONOMIC DIMENSIONS OF POVERTY IN NEPAL: A LOGISTIC REGRESSION ANALYSIS - Gajurel , Ram Prasad; Niroula , Anil; Dangal , Dil Nath; Poudel , Tanka Mani; Lamichhane, Kul Prasad (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Poverty, a multifaceted concept influenced by several socioeconomic factors, is not only an outcome of individual destiny but also socioeconomically created by severe deprivation of basic needs. Individuals could escape poverty and enhance the quality of life through the government’s ample policy interventions. This study examines socioeconomic determinants of poverty in Nepal from multidimensional perspectives. Using household survey data—9600 households—from Nepal Living Standards Survey IV 2022/23, this study applied binary logistic regression analysis. Considering approximately 18% of poor and 82% of nonpoor households, the results revealed the poverty status of households could not be significantly influenced by demographic factors, such as age, gender, and marital status. Rather, poverty status might be influenced by family size, residential status, remittance, nonfarm or side business, agricultural landholdings and livestock, access to electricity, better health and road infrastructure, dwelling status, and preference for cooking fuel. Thus, it is observed that the households may fall into poverty due to higher family dependency, urban residency, agro-landholdings and livestock, firewood as cooking food, availability of the dwelling, and larger family size with the remittance—and that they would walk away from poverty thanks to remittance, family business, electricity, adequate road, and health facilities. This study's findings suggest that nonfarm businesses, less agricultural dependence strategies and programs, and the promotion of physical and social overheads are crucial for achieving Nepal's sustainable development goals by reducing multidimensional poverty.  JEL Classification Codes: C55, I32, R20, R28.